Impact of light spectral combinations on morphology, yield, and quality of indoor-grown cilantro - Akter, Nazmin; Cammarisano, Laura; Taylor, Gail; Naznin, Most Tahera; Verdonk, Julian C.; Ahamed, Md Shamim (Frontiers in Sustainable Food Systems, 2024)
Advanced indoor farming systems utilizing artificial lighting to produce high-quality crops are rapidly gaining research interest. Specific light spectra from artificial lights can create optimal conditions for indoor plant cultivation. Cilantro, an herb widely used in the culinary industry for its distinct fresh flavor and high nutritional content, has been the subject of numerous studies examining the effects of different ratios of blue (B, 400–500 nm) and red (R, 600–700 nm) light on its growth. However, the impact of adding far-red (FR, 700–780 nm) light has not been fully explored. This study aimed to determine the optimal light spectral combinations for enhancing the morphology, yield, phytochemical content, and shelf life of indoor-grown cilantro. Three light spectral treatments [R:B:FR = 4:1:0 (R4B1), R:B:FR = 4:0.5:0.5 (R4B0.5FR0.5), and R:B:FR = 3:1:1 (R3B1FR1)] were evaluated at a consistent Photon Flux Density of 160 ± 10 μmol m−2 s−1 using broad-spectrum LED lamps. The growth chamber conditions during light treatments were maintained at an average temperature of 23°C, relative humidity of 49%, and CO2 concentration of 575 ppm, with a 16/8 h (light/dark) photoperiod. Growth, yield, and various quality parameters of cilantro were measured. Results indicated that the R3B1FR1 and R4B0.5FR0.5 treatments increased plant height, leaf area, and yield by 88 and 29%, respectively, compared to the R4B1 treatment. Conversely, R4B1 positively influenced quality parameters and shelf life. The study concluded that R3B1FR1 had a more substantial positive effect on cilantro yield than R4B0.5FR0.5 and R4B1, although the light treatments statistically unaffected quality parameters and shelf-life.